Peran teknologi informasi dalam peningkatan mutu pelayanan rumah sakit: A literatur review - Teresa, Teresa; Ridwan, Muhammad (Holistik Jurnal Kesehatan, 2025)
Background: Digital transformation in the healthcare sector has accelerated significantly, particularly following the COVID-19 pandemic, which has driven hospitals to adopt information technology (IT) extensively. IT has become a transformative solution for improving reciprocal care, operational efficiency, and patient data security through the integration of various systems, from Electronic Medical Records (EHR), Hospital Management Information Systems (SIMRS), telemedicine, to mobile applications and Clinical Decision Support Systems (CDSS). IT implementation has been shown to improve patient safety, diagnostic accuracy, service efficiency, and patient satisfaction, but also presents challenges related to user adaptation, system integration, and data security. Purpose: To provide information on the role of technology in improving the quality of hospital services, along with the challenges and opportunities for its implementation. Methods: A systematic review using a systematic search of the databases PubMed, ScienceDirect, ProQuest, and Scopus. Articles meeting the inclusion criteria were selected and published between 2020 and 2025. The search technique used the PRISMA scheme. Results: Four articles, with a total of 460 participants, were identified that examined the impact of information technology on hospital service quality. They demonstrated that information technology, including management information systems, EMRs, patient monitoring applications, and mobile patient-doctor communication applications, effectively improved patient satisfaction, safety, and operational efficiency. Conclusion: The implementation of information technology (IT) in hospitals has been proven effective in improving service quality by increasing efficiency, patient safety, patient satisfaction, and medical staff performance.   Keywords: Electronic Medical Records; Hospital Service Quality; Information Technology; Management Information Systems; Patient Satisfaction.   Pendahuluan: Transformasi digital di sektor kesehatan mengalami percepatan signifikan, terutama pasca pandemi COVID-19, yang mendorong rumah sakit mengadopsi teknologi informasi (TI) secara masif. TI menjadi solusi transformatif untuk meningkatkan mutu pelayanan, efisiensi operasional, dan keamanan data pasien melalui integrasi berbagai sistem, mulai dari Rekam Medis Elektronik (EHR), Sistem Informasi Manajemen Rumah Sakit (SIMRS), telemedicine, hingga aplikasi mobile dan Clinical Decision Support Systems (CDSS). Implementasi TI terbukti meningkatkan keselamatan pasien, akurasi diagnosis, efisiensi pelayanan, serta kepuasan pasien, namun juga menghadirkan tantangan terkait adaptasi pengguna, integrasi sistem, dan keamanan data. Tujuan: Memberikan informasi tentang peran teknologi informasi dalam meningkatkan mutu pelayanan rumah sakit serta tantangan dan peluang implementasinya. Metode: Systematic review pada pencarian sistematis melalui database PubMed, ScienceDirect, ProQuest, dan Scopus, dengan artikel yang memenuhi kriteria inklusi dengan publikasi antara 2020 sampai 2025 serta teknik pencarian artikel dengan tahapan skema PRISMA. Hasil: Mengidentifikasi empat artikel dengan total 460 peserta yang meneliti pengaruh teknologi informasi terhadap mutu pelayanan rumah sakit yang menunjukkan teknologi informasi, termasuk sistem informasi manajemen, EMR, aplikasi monitoring pasien, dan aplikasi mobile komunikasi pasien-dokter, efektif meningkatkan kepuasan pasien, keselamatan, dan efisiensi operasional. Simpulan: Penerapan teknologi informasi (TI) di rumah sakit terbukti efektif meningkatkan mutu pelayanan melalui peningkatan efisiensi, keselamatan pasien, kepuasan pasien, dan kinerja tenaga medis.   Kata Kunci: Kepuasan Pasien; Mutu Pelayanan Rumah Sakit; Rekam Medis Elektronik; Sistem Informasi Manajemen; Teknologi Informasi.